MENINGKATKAN MINAT SISWA DALAM PEMBELAJARAN AL-QURAN HADIST MELALUI MODEL PEMBELAJARAN DI MTSN 2 AGAM - Suteguh , M. Ibnu; Trisno, Bambang; Yusra, Syaifullah (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
Based on the results of observations that researchers made when carrying out PPL (Practical Field Experience) activities at MTsN 2 Agam, there were quite a few students who seemed less interested in learning Al-Quran Hadith, because the learning was too monotonous. This can be seen during learning activities, seen from the attitudes and behavior of students who pay less attention to the teacher's explanation of the material. This can happen due to a teacher's lack of creativity in designing and planning learning, so that the ongoing learning becomes boring. In this research, the researcher used the SLR (Systematic Literature Review) research method with the aim of studying increasing students' interest in learning Al-Quran Hadith with the learning model applied in learning. Researchers collected references from several journals and these journals have been published online. The researchers collected references for this article using Google Scholar. The research results that the researchers obtained were that there was a positive relationship between the use of learning models and the results obtained by students. This means that if the application of the learning model used by educators is in accordance with the learning material, students will feel interested in learning because with learning media the learning atmosphere will be more conducive and enjoyable.